Arrayed waveguide grating - Mohamed Abdelaziz, Yassir Abdelrahim (2008)
If compared to other kinds of communication networks, it is found that fiber optics networks are the most rewarding communication networks, since It has been suggested that if the full potential of fiber optic communication is realized, a single fiber would be sufficient to serve the needs of telecommunication users (heavy data traffic demands) throughout the world. Fiber optics is the channeled transmission of light through hair thin glass. The explosive growth of optical networks has brought forward an increased need for guided wave optical components for the sake of multiplexing and routing. Arrayed waveguide grating is one of the component that serves as a multiplexer and de-multiplexer, also if connected with other device can work as an add drop multiplexer for dense wave length division multiplexing, This is due to the fact that AWG-based devices have been proven to be capable of precisely de-multiplexing a high number of channels, with relatively low loss. The purpose of this project is to investigate the operation function of the arrayed waveguide grating and understand the performance parameters of the device, and then we investigate those performance parameters and try to find out how those parameters can affect crosstalk of the device. We make our study about only the crosstalk because crosstalk is the most important parameter that can affect the overall performance of the device. We used the waveguide spacing as a key that relates all other parameters to the crosstalk, since there is an inverse relationship between the spacing and the crosstalk. The result from this project is that there should be a tradeoff between the crosstalk and the waveguide spacing, where small waveguide spacing is required for compact design, and at the same time whenever the spacing is small crosstalk will be high.